2003
DOI: 10.1146/annurev.genet.37.050503.084247
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Gene Transfer and the Origins of Prokaryotic Groups

Abstract: Lateral gene transfer (LGT) is now known to be a major force in the evolution of prokaryotic genomes. To date, most analyses have focused on either (a) verifying phylogenies of individual genes thought to have been transferred, or (b) estimating the fraction of individual genomes likely to have been introduced by transfer. Neither approach does justice to the ability of LGT to effect massive and complex transformations in basic biology. In some cases, such transformation will be manifested as the patchy distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
260
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(275 citation statements)
references
References 136 publications
13
260
0
2
Order By: Relevance
“…Vestergaard et al (2014) also classified the cas subtypes based on cas-protein occurrences for archaea. Phylogenetic analysis of this study also revealed that many functions of the identified cas proteins could be derived from distantly related genomes, plasmids and phages that was agreed to earlier findings (Nelson et al 1999;Zivanovic et al 2002;Boucher et al 2003;Marraffini and Sontheimer 2009;Chellapandi and Ranjani 2011;Spilman et al 2013). Euryarchaea are more diverse phylogenetically than crenarchaea because of they are generally heterotophic in nature and frequent a wide range of natural environments (Vestergaard et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Vestergaard et al (2014) also classified the cas subtypes based on cas-protein occurrences for archaea. Phylogenetic analysis of this study also revealed that many functions of the identified cas proteins could be derived from distantly related genomes, plasmids and phages that was agreed to earlier findings (Nelson et al 1999;Zivanovic et al 2002;Boucher et al 2003;Marraffini and Sontheimer 2009;Chellapandi and Ranjani 2011;Spilman et al 2013). Euryarchaea are more diverse phylogenetically than crenarchaea because of they are generally heterotophic in nature and frequent a wide range of natural environments (Vestergaard et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, traits that are less conserved will be found in small phylogenetic clades ( Figure 1-trait B). Finally, gene loss, convergent evolution and lateral gene transfer can result in the distribution of many traits across multiple phylogenetic groups (Doolittle, 1999;Snel et al, 2002), leading to random associations between phylogenetic and functional relatedness (Boucher et al, 2003) (Figure 1-trait C).…”
Section: Introductionmentioning
confidence: 99%
“…If phylogenetic conservation is related to genetic complexity as predicted by Martiny et al (2012), then enzyme-positive genotypes should be associated with small clades (Figure 1b) since extracellular enzyme production is commonly encoded by a few genes (see references in Supplementary Tables S1-S3). Alternatively, the traits under investigation may be randomly associated with prokaryotic taxa (Figure 1c), possibly resulting from frequent gene gain/loss, rapid convergent evolution or horizontal gene transfer that obscure vertical inheritance (Doolittle, 1999;Gogarten et al, 2002;Snel et al, 2002;Boucher et al, 2003).…”
Section: Introductionmentioning
confidence: 99%